PENGARUH PENGALAMAN AUDITOR DALAM MERESPON INFORMASI PERSUASIF AUDITEE - Sigit Wira Pratama; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
In practice, Auditor’s perception and preference about the degree of importance of government procurement control system are different between them. And dualism of information that auditee gives to auditor, makes auditor have to respon in manner of completion of audit task and provided assurance opinion. Many factors, that influence auditor’s perception and respon, one of them is auditor’s audit experience. This study examines how auditor’s audit experience influence auditor perception and preference about the degree of importance of government procurement control system and influence in auditor’s respon about persuasiveness of information provided by auditee. Research sample are auditors who work in Indonesian Supreme Audit Board (head office and representative office). The result indicates that auditor’ experience have influence auditor’s respon in two condition management low and high ratings. However, this study do not explain the influence of auditor’s experience in perception and preference about the degree of importance of government procurement control system.